1983
DOI: 10.1073/pnas.80.1.173
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond photolysis of CO-ligated protoheme and hemoproteins: appearance of deoxy species with a 350-fsec time constant.

Abstract: Photolysis ofHbCO, MbCO, and CO-protoheme has been investigated by measuring transient differential spectra and kinetics of induced absorption after excitation with. a 250-fsec laser pulse at 307 nm. Probing was performed by a part of a continuum pulse between 395 and 445 nm. Photodissociation of the three liganded species occurred within the pulse duration. By contrast, the formation ofdeoxy species appeared with a mean (± SD) response time of 350 ± 50 fsec. This time constant was identical for the three spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
154
1
3

Year Published

1984
1984
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(169 citation statements)
references
References 18 publications
11
154
1
3
Order By: Relevance
“…The calculations of Im-FeP-XO (X ϭ C, N, and O) models consider geometries at Q P ϭ 0.2 and 0.4 Å to include two possible out-of-plane geometries. Given the rapidity of photolysis, it is reasonable to assume that the spin state of the iron is randomized relative to that of the photolyzed ligand (2,50). The assumption that the spin states of the free ligands and the iron are uncorrelated implies that possible spin states are S Fe ϩ S ligand , S Fe ϩ S ligand Ϫ 1, .…”
Section: Discussionmentioning
confidence: 99%
“…The calculations of Im-FeP-XO (X ϭ C, N, and O) models consider geometries at Q P ϭ 0.2 and 0.4 Å to include two possible out-of-plane geometries. Given the rapidity of photolysis, it is reasonable to assume that the spin state of the iron is randomized relative to that of the photolyzed ligand (2,50). The assumption that the spin states of the free ligands and the iron are uncorrelated implies that possible spin states are S Fe ϩ S ligand , S Fe ϩ S ligand Ϫ 1, .…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] The binding of a small ligand to heme proteins has been greatly studied in order to understand the relationships between protein structure, dynamics, and function. 2,3,[5][6][7][8][9][10][11][12][13][14] In particular, the rebinding dynamics of a number of neutral diatomic molecules, such as CO, NO, or O 2 to ferrous heme or heme proteins has been widely investigated both experimentally and theoretically. By contrast, only a few experiments have been carried out on the rebinding dynamics of ionic molecules to heme proteins.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that 35 ps after the light pulse, a transient spectrum was observed with a band maximum located at 765 nm, i.e., red shifted by almost 6 nm relative to the deoxy HbA band 111. This transient remained unchanged up to 60 ns, indicating that the geometry of the heme group is only partly relaxed and that equilibration of the surrounding protein structure occurs on a longer time scale (Sawicki &Gibson, 1976;Martin et al, 1983;Petrich et al, 1991). Figure 2 shows the equilibrium characteristics of band I11 in the deoxy HbA (maximum absorbance at 760 nm) compared to that of the deoxy p4 tetramer, which is red shifted infrared by almost 6 nm, i.e., at nearly the same wavelength as the 35 ps transient reported by Dunn and Simon (1991) after photodissociation of CO HbA.…”
Section: Resultsmentioning
confidence: 99%